(untitled) (Future Cities and Environment, 2024)
The ever-evolving threats presented by climate change compel us to rethink and restructure our built environment, particularly housing designs, to imbue them with resilience and adaptability. In this research, this study has embarked on an exhaustive review of scholarly works to identify design harmonies that can enhance the resilience of housing structures under fluctuating climate circumstances, particularly flooding results from unexpected heavy rains. The study’s purview extends to diverse case studies from Northern and Southern parts of Pakistan experienced unprecedent rains and flooding, elucidating the unique obstacles and environmental variances across these regions. The literature review spans across several disciplines, exploring resilience in housing design from architectural, environmental, health and socio-economic angles. It provides an in-depth examination of established methodologies and innovative trends, with an emphasis on merging ancestral wisdom with modern advancements. This holistic approach underscores the significance of community-based design solutions, active community involvement, and policy structures in cultivating resilience. The case studies from different flood affecting regions of Pakistan serve as practical examples, shedding light on the unique climatic adversities and identifying 14 critical housing defects caused by natural disasters. By juxtaposing these diverse climatic settings, this study determine design and protection guidelines that can be customized to cater to each region’s specific requirements, fostering a resilient housing infrastructure capable of weathering climate change impacts. In conclusion this study underscores the importance of adopting both immediate and long-term strategies for housing design in response to climate change. By synthesizing the valuable insights gleaned from the literature review and case studies, a set of recommendations for architects, urban planners, and policymakers are suggested to promote resilient housing design, not only within Pakistan but on a global scale.